Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L) Asal Biji (True Shallot Seeds) Pada Berbagai Macam Pupuk NPK - Triyono, Kharis; Santosa, Sartono J; Maulida, Elly E (JURNAL BUDIDAYA PERTANIAN, 2025)
Shallots (Allium ascalonicum L. syn. A. cepa var. aggregatum) are a strategic commodity and has high economic value and cannot be substituted with other commodities. Currently, shallots are included in the main food commodity group, because their availability and price greatly influence inflation and the national economy. However, shallot production remains low, and planting material from tubers is expensive and susceptible to pests and diseases. The aim of this research is to increase shallot production by using planting material from True Shallot Seed (TSS) seeds through testing various types of NPK fertilizer on shallot growth and yield). This research aimed to increase shallot production by utilizing True Shallot Seeds (TSS) as planting material and evaluating the effects of various NPK fertilizer types on shallot growth and yield. The research design used was a single factor Randomized Block Design with 4 treatments and 6 replications so that there were 24 experimental units. Variables observed included plant height, number of leaves per clump, number of tubers per clump, tuber diameter, fresh tuber weight per plant, fresh weight of stover and dry weight of stover. The observation results were tested using Analysis of Variance (Anova) if there was a significant difference followed by Duncan's 5% multiple range test. The results indicated that the treatments had a highly significant effect on the growth and yield of shallot plants derived from TSS .The type of NPK fertilizer had a significant effect on the variables of plant height, number of tubers per hill, fresh weight of tubers and dry weight of plant stover and did not significantly differ on the parameters of number of leaves, diameter of tubers and fresh weight of stover. The highest yield was in the M3 (mixed NPK) treatment, namely the number of tubers was 15.89 and the fresh weight of the tubers was 164.11 gr